Suistainable Tourism Deswita Berkembang menjadi Deswita Maju di Desa Wisata Sumberbulu - Erna Wigati; Wahyu Ari Indriastuti (Media Wisata, 2021)
This study aims to determine the quality of Sumberbulu tourism village in contributing to social welfare by having a local and regional economic network. Methods used in this research is to use descriptive qualitative method, with data analysis done inductively. The aim is to find out sustainable tourism village to develop into the tourism village of Sumberbulu Karanganyar. The result this study, Sumberbulu tourism village, in contributing to economic and social welfare has inderectly been seen by the presence of many buyers who buy ornamental plants when visiting Sumberbulu Village and orrdering snacks that have been produced by community members from the formation of small culinary teams from several residens houses. The quality of the tour guides in the Sumberbulu tourist village is not yet visible because everything is still one with Pokdarwis. The quality of accommodation (homestay) in the tourist village of Sumberbulu is getting better and better because the homestay management team continuously checks it from the homestay coordinator who has been formed from Pokdarwis